On collective forms of the Chopin cult in Poland during the nineteenth century - Dziadek, Magdalena (Interdisciplinary Studies in Musicology, 2018)
This article is devoted to specific forms of the Chopin cult that developed in Poland during the nineteenth century. Due to the socio-political situation in the country during the period of the Partitions and the influence of tradition, this cult was manifest first and foremost in the joint experiencing of anniversaries connected with the composer on the part of members of local communities or the entire nation. The basic medium of that experience was the press, in which biographic articles, sketches on his music and also poetical works devoted to the composer were an obligatory part of the anniversaries of Chopin’s birth and death. In this way, the Chopin cult in Poland became primarily a literary phenomenon. Also linked to the traditional culture of the letter that was Polish culture of the nineteenth century is the characteristic form of the Chopin cult known as the obchod. The communal character of the obchod was reflected in its specific form and content. One of the prime concerns was the need to forcibly communicate the fact that Chopin’s music was a national good. Thus at the centre of the theatrically-managed obchod stood an orator or actor declaiming against the background of Chopin’s music. For the purposes of these declamations, a huge amount of literature was produced, examples of which are discussed in the article. Another characteristic “anniversary” product were re-workings of Chopin compositions for large orchestral and choral forces, treated as “ceremonial”. One example of a Chopin celebration displaying the features discussed were the Lviv Chopin celebrations in 1910, which the author describes in more detail.